Optimal Inflation Tax Under Precommitment: Theory and Evidence - Calvo, Guillermo A.; Leiderman, Leonardo (American Economic Review, 1992)
We develop and test the orthogonality conditions implied by a dynamic model of the inflation tax. A distinguishing feature of the analysis is that the welfare loss from inflation, the money-demand function, and the time path of inflation are jointly derived from first principles of government and private-sector intertemporal optimization. Quarterly data for Argentina, Brazil, and Israel are used in implementing the model. Although the overidentifying restrictions of the model are not rejected in most cases, there are several data points characterized by higher rates of inflation than the optimal rates under precommitment.